Studies on Sandal Spike Incidence of the Spike Disease Versus the Major and Minor Nutrient Status of the Soils of Sandal Growing Regions - Parthasarathi, K.; Gupta, S. K.; Rajeevalochan, A. N.; Rao, P. S. (Indian Forester, 1973)
A study of the major and minor nutrient status of the soils of spike-affected and spike-free sandal growing regions has shown that deficiency of either the major nutrients, N,P,K and Ca, or the minor nutrients, Cu, Zn, Mn, Mo and Co in the soils of the spike-affected sandal regions is not serving as a pre-disposing factor for the onset of sandal spike disease. Khan and Yadav (1962) reported that calcareous soils with a low amount of available nutrients were related to the incidence of spike disease in sandal. The soils of the Mysore State are generally not calcareous in nature, but spike disease exists in many of the districts of the State. It has, therefore, given rise to a doubt as to whether the composition of the soil bas really anything to do with the incidence or otherwise of the spike disease in sandal. As long ago as 1955, Muthanna reported that application of minor elements did not show any remedial effect on the sandal affected by spike disease, thus showing that the latter is not traceelement deficiency disease. That the disease is not a deficiency disease is further proved by the fact that it is transmissible (Coleman, 1917; Sreenivasaya and Gopalaswami Naidu, 1928), while deficiency diseases are not. The question, however, remains as to whether the soil status is serving as a pre-disposing factor for the onset of the disease, though not the cause for it. Hence experiments have now been conducted with a view to settling this question, examining the soil samples from some of the districts of the healthy sandal areas (Bellary, Dharwar and Shimoga), and some of the districts of the spiked sandal areas (Kolar, Tumkur and Bangalore) in the Mysore State. From each of the districts, a suitable forest region was chosen, and soil samples were taken from two spots, collecting them from three different layers (0-25 cm, 25-55 cm, 55-85 cm) after clearing the surface soil. The analysis of the soil samples for pH, major nutrients (N,P,K and Cal and minor nutrients (Cu, Zn, Mn, Mo and Co) was done following the methods described by Jackson (1967) and Holmes (1945). Since the pH of the soils of the Mysore State ranges from 5.6 to 6.8 at which range the nutrients (major and minor) are well available, only the total status of these nutrients has been determined. The pH was determined at the moisture saturation percentage of the soils according to the procedure described by Jackson (1967).